2016
DOI: 10.4149/bll_2016_106
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine protected COPD-induced lung injury by regulating miRNA-146a

N Li1,
et al.

Abstract: OBJECTIVE: To study the mechanism of protection provided by dexmedetomidine against COPD-induced lung injury. METHODS: COPD rat model was determined by measuring lung function, and comparing HE staining between two different groups. We got the lung tissue and cells from the control and COPD groups. The cells were divided into three groups: control group, and blank and drug groups that were from the COPD rats. Cell apoptosis, relative gene expression and TNF-α and IL-1β from nutrient solution were measured. Chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Many reports have noted other possible applications including use as a protective agent against ischemia/ reperfusion (I/R) injury in various organs [10,11], including heart [12], kidney [13], brain [14], lung [15], liver [16], and even retina [17]. Only three studies have addressed the roles of miRNAs in mechanisms of organ protection [14,18,19]. Moreover, no clinical trials have focused on miRNA expression profiling after administration of dexmedetomidine, and there are no studies on the effects of dexmedetomidine on circulating miRNAs.…”
Section: Rongbi Liangmentioning
confidence: 99%
“…Many reports have noted other possible applications including use as a protective agent against ischemia/ reperfusion (I/R) injury in various organs [10,11], including heart [12], kidney [13], brain [14], lung [15], liver [16], and even retina [17]. Only three studies have addressed the roles of miRNAs in mechanisms of organ protection [14,18,19]. Moreover, no clinical trials have focused on miRNA expression profiling after administration of dexmedetomidine, and there are no studies on the effects of dexmedetomidine on circulating miRNAs.…”
Section: Rongbi Liangmentioning
confidence: 99%
“…It can activate the presynaptic α 2 receptors in peripheral sympathetic endings, inhibit the release of norepinephrine, and decrease the concentration of plasma catecholamine ( Giovannitti et al, 2015 ). Furthermore, it can stabilize hemodynamics, relieve oxidative stress caused by surgical trauma, ( He et al, 2021 ), reduce the synthesis and release of pro-inflammatory factors (e.g., TNF-α and IL-6) ( Xu et al, 2019 ), and protect the lung through multiple ways, including anti-sympathia and inhibition of apoptosis, oxidative stress, and inflammatory response ( Li et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nalbuphine mainly activates κ opioid receptors and produces spinal analgesia ( He et al, 2021 ). Because of its long duration and few adverse reactions, it can be used before operations ( Xu et al, 2019 ) to effectively prevent anesthesia stimulation and central sensitization caused by operation trauma as well as reduce the intraoperative inflammatory response ( Li et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…[ 19 ] The pain associated with thoracic surgery may release the inflammatory factors that might suppress the pulmonary function. [ 20 ] Thus, both laboratory and clinical studies suggested that dexmedetomidine may exert a protective effect on the pulmonary system,[ 21 22 ] leading to a reduced incidence of respiratory complications. The ischemic preconditioning combined with dexmedetomidine might decrease the incidence of postoperative pulmonary complications by alleviating the inflammatory response and oxidation reaction, which are corroborated by the prevention of the surge of interleukin-6 (IL-6) and enhancement of the activation of superoxide dismutase.…”
Section: Orbidity a Ssociated With mentioning
confidence: 99%